Natural history of autoimmune atrophic gastritis: a prospective, single centre, long‐term experience. Issue 11 (17th October 2019) - Miceli, Emanuela; Vanoli, Alessandro; Lenti, Marco Vincenzo; Klersy, Catherine; Di Stefano, Michele; Luinetti, Ombretta; Caccia Dominioni, Costanza; Pisati, Martina; Staiani, Martina; Gentile, Antonella; Capuano, Francesca; Arpa, Giovanni; et al.
Summary: Background: Autoimmune atrophic gastritis (AAG) is an immune‐mediated disorder characterised by destruction of gastric oxyntic mucosa Aim: To explore gastric histopathological evolution in a cohort of AAG patients over a prolonged follow‐up Methods: Single centre prospective study enrolling consecutive patients with histologically confirmed AAG between 2000 and 2018. All AAG patients undergoing endoscopic follow‐up every 1‐3 years were classified as having stages 1, 2 or 3 according to atrophy severity (mild, moderate and severe). AAG patients with either glandular or neuroendocrine dysplasia/neoplasia were classified as having stage 4. Disease stage progression, and changes in serum anti‐parietal cell antibody (PCA), chromogranin A and gastrin‐17 were assessed. Results: In total, 282 AAG patients (mean age 60.3 years; F:M ratio 2.4:1; median follow‐up 3 years, interquartile range 1‐7) were enrolled. All patients with stages 1 or 2 progressed to stage 2 or 3 over time with a steady trend ( P  = .243) and regression from a severe to a milder stage was never noticed. Disease progression of patients with stages 1 or 2 occurred within the first 3 years. PCA positivity rate did not change over time. Stage 3 patients had higher gastrin‐17 levels compared to patients with stages 1 and 2 (median 606 vs 295 pg/mL; P  < .001). In stage 3, the hazard ratio for the risk of developing stage 4 was 6.6 (95% CI 1.5‐29; P  = .001). Conclusions: AAG is a steadily progressive disease, in which stages 1 and 2 always progress to stage 3. The risk of developing a complicated disease stage is greater in patients with more severe gastric lesions.